Expert systems application for structural, transportation, and environmental engineering - M Arockiasamy (CRC Press, 1992)
The book is structured in seven chapters with a comprehensive presentation of expert system applications. Chapter 1 describes the expert systems components including the characteristics of expert systems. Chapter 2 presents the expert system methodologies for design application, and selected applications to structural design. Chapter 3 covers design standards to improve the representation, organization, analysis and use of standards. Chapter 4 outlines typical expert systems intended for construction engineering and management applications. Chapter 5 includes the main concepts underlying the expert systems with emphasis on bridge analysis, rating, and management. Chapter 6 describes expert systemsmethodology and applications which aid the transportation and highway engineer planning, design, and operation. And Chapter 7 focuses on several applications of expert in the fields of environmental and water resources engineering